2011
DOI: 10.1111/j.1524-4741.2010.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonobreast: Predicting Individualized Probabilities of Malignancy in Solid Breast Masses with Echographic Expression

Abstract: To create an individualized predictive tool for the risk of malignancy in solid breast masses, based on echographic and clinical characteristics. Research Ethics Committee approval and informed consent were obtained. This multi-center study included 1,403 solid breast masses prospectively. Each ultrasound feature was analyzed and compared with the definitive diagnosis. The ultrasound results, women's ages and family histories of breast cancer were included in a multivariate logistic regression model. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Although we found statistically significant correlations between malignancy rate and tumor size and patient age respectively in the binary logistic regression analysis, it was not possible to establish a cut-off-value for those criteria while retaining an acceptable sensitivity and specificity. Paulinelli et al did not find any tumor size that could be significant in the multivariate analyses, but did find an increasing risk of malignancy with increasing age (ROC giving a sensitivity of 84.5 %, a specificity of 64.5 % and an overall accuracy of 74.5 % for the age of 40) [11]. We found that the combination of oval/round shape and circumscribed margin without echogenic rim ( = circumscribed margin in the 5th edition of the ACR BIRADS ® Atlas) [8] was the most reliable to predict a benign outcome with a negative predictive value (NPV) of 99.1 %.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although we found statistically significant correlations between malignancy rate and tumor size and patient age respectively in the binary logistic regression analysis, it was not possible to establish a cut-off-value for those criteria while retaining an acceptable sensitivity and specificity. Paulinelli et al did not find any tumor size that could be significant in the multivariate analyses, but did find an increasing risk of malignancy with increasing age (ROC giving a sensitivity of 84.5 %, a specificity of 64.5 % and an overall accuracy of 74.5 % for the age of 40) [11]. We found that the combination of oval/round shape and circumscribed margin without echogenic rim ( = circumscribed margin in the 5th edition of the ACR BIRADS ® Atlas) [8] was the most reliable to predict a benign outcome with a negative predictive value (NPV) of 99.1 %.…”
Section: Discussionmentioning
confidence: 94%
“…In this study we wanted to analyze the influence of lesion size alone and in combination with patient age to find a "rule of thumb" for the combined mammography-ultrasound screening setting. We did not try to establish a new kind of prediction model like other authors have designed [11]. Instead we assessed whether it was possible to recommend a cut-off value for size (and/or age), under which it is reasonable to obviate a needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…23 It was normally interpreted as high proliferation which led to expansive growth against peripheral tissues 24 and thus was always considered as a risk sign for BC. 25,26 Meanwhile, studies have also manifested that vertical orientation was significantly associated with more invasive proportion of tumor 27 and higher level of clinical risk in BC. 28 However, evidence concerning vertical orientation and clinical outcomes in BC was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The field of ethics studies the principles of right and wrong [20,21] in the field of medicine refers to the ethics between the doctor-patient relationship, including all general responsibilities towards the patient [22]. Medical ethics includes four principles: Respect for autonomy, beneficence, non-maleficence, and justice [23].…”
Section: Ethicsmentioning
confidence: 99%